Entrepreneurship development and small business enterprises - Charantimath, Poornima M. (New Delhi : Pearson, 2018)
The revised and updated third edition of entrepreneurship development and small business enterprises discusses how entrepreneurs can successfully manage their ventures in a highly dynamic and challenging environment. This book prepares students for life outside the classroom through case studies drawn from diverse sectors, profiles of successful entrepreneurs and projects that promote analysis and decision making. Thorough coverage of the conceptual framework of entrepreneurship development and casual and effectual entrepreneurship. Each Chapter begins with a picture serve as ice-breakers and narrate the key concepts of the Chapter through a powerful story around an entrepreneur or company for better understanding of the Chapter new end-of-chapter activities and projects designed to promote effectual Reasoning. Fourteen end-of-chapter case studies drawn from diverse sectors reflect current thinking and practice in the Indian context. Each Chapter contains several boxes that highlight the latest developments, interesting stories and quotes of the entrepreneurs mentioned in the beginning of the Chapter the manufacturing and service sectors have been covered in greater detail by showcasing real-world examples and case studies from Indian and global enterprises. Online supplement consisting of instructors$1 (Bmanual and power point lecture slides to support interactive training and teaching. Table of Contents: 1 entrepreneurship 2 entrepreneurial development and Training 3 women entrepreneurs 4 family business 5 micro, small and medium enterprises 6 identification of business opportunities 7 Business plans 8 Project management and financing 9 institutions supporting business enterprises 10 Business organizations and business laws 11 preventing sickness in enterprises 12 Financial Management in enterprises 13 operations and human Resource Management in enterprises 14 Managing marketing and growth in enterprises.s
Keywords: Entrepreneurship; Entrepreneurship Management; Small Business Enterprises